Dilemma In Superiority: Rank, Grandiosity, And Aggression Among Men In Uniform - Kaye Marie Aguirre; Audrey Elaisa Hiponia; Czyne Javier; Hannah Mae Lendio; Mary Glenda A. Lugtu; Vincent Sales; Neil Brianne Vedeja (Research Synergy Foundation, 2023)
Aggressive, fierce, and grandiose are the words that are often associated with our men in uniform. Law enforcement officers have enough authority and power that can be used against citizens. They are being severely stigmatized by these controversies, and people are generalizing police organizations. Despite the effort to protect the country, it was reciprocated with prejudice and misconception. The purpose of this study was to determine the level of aggression and grandiosity in terms of sex and rank; also to find out if there is a significant relationship between rank, grandiosity, and aggression. The researchers used purposive sampling to choose the respondents. The participants are policemen who have a position and/or rank in a certain PNP office and are available during the conduct of the on-site survey. A set of research questionnaires were distributed to the Philippine National Police of General Santos City-Camp Lira with a total of 55 participants. The responses were analyzed through the use of SPSS. Multiple regression analysis proves that the variables rank, grandiosity, and aggression are significant, < 0.001, and reject the null hypothesis. Additionally, through deeper analysis, only the variables aggression and grandiosity have a significant relationship.